2020
DOI: 10.1088/1361-6528/ab7fcf
|View full text |Cite
|
Sign up to set email alerts
|

Neutral oxygen irradiation enhanced forming-less ZnO-based transparent analog memristor devices for neuromorphic computing applications

Abstract: Surface oxidation employing neutral oxygen irradiation significantly improves the switching and synaptic performance of ZnO-based transparent memristor devices. The endurance of the as-irradiated device is increased by 100 times, and the operating current can be lowered by 10 times as compared with the as-deposited device. Moreover, the performance-enhanced device has an excellent analog behavior that can exhibit 3-bits per cell nonvolatile multistate characteristics and perform 15 stable epochs of synaptic op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…The comparative advantage of the NPs’ incorporation is the ability to emulate both STP and LTP artificial synaptic responses in one single switching mode [ 55 , 56 ]. Similar results have been also reported for other material configurations [ 57 , 58 , 59 ]. Moreover, we have to underline that Pt NPs facilitate the charge transfer from the BE to SiO 2 , since a lower interface barrier is formed [ 60 ], in terms of height, which increases the transmission probability for electron tunneling.…”
Section: Discussionsupporting
confidence: 91%
“…The comparative advantage of the NPs’ incorporation is the ability to emulate both STP and LTP artificial synaptic responses in one single switching mode [ 55 , 56 ]. Similar results have been also reported for other material configurations [ 57 , 58 , 59 ]. Moreover, we have to underline that Pt NPs facilitate the charge transfer from the BE to SiO 2 , since a lower interface barrier is formed [ 60 ], in terms of height, which increases the transmission probability for electron tunneling.…”
Section: Discussionsupporting
confidence: 91%
“…In order to realize memristor-based neuromorphic system, the device should exhibit gradual change in conductance states; the gradual behavior is also termed as analog switching, meanwhile, abrupt change in conductance states is called as digital switching. 12,13 Henceforth, careful engineering in the formation and rupture of conductive filament/bridge to achieve gradual switching is required. 14 Several techniques are recently reported that digital switching can be transformed into analog switching in memristor devices either by using annealing processes, different doping concentrations, or different top electrodes.…”
mentioning
confidence: 99%
“…Nevertheless, some studies have shown that the modification and manipulation of the TCO electrodes may trigger the oxygen vacancy concentration, thus, enhancing the device performance [242], [256], [257]. Various methods were proposed to deposit ZnO switching layer on TCO electrodes, like the solution-processed (sol-gel) method [167], [189], [246], [258]- [260], high-power pulse laser deposition (PLD) [238], [261]- [263], atomic layer deposition (ALD) [264], thermal-roll lamination technique [265], hydrothermal growth [266], RF magnetron sputtering [53], [151], [202], [205], [267]- [270], metal-organic chemical vapor deposition [271]- [273]. The introduction of gallium into zinc oxide shows to improve the transmittance of the film.…”
Section: F Transparent/flexible Zno Based Rrammentioning
confidence: 99%